AGRARIAN DISTRESS: A CASE STUDY OF INDEBTEDNESS AMONGST FARMERS IN HARYANA STATE - Jakhar, Babloo; Kait, Rohtas; Lal, Choote (Economics of Agriculture, 2023)
This study addresses the critical issue of farmer indebtedness as the primary cause of agrarian distress in Haryana, India. The pervasive challenge of debt negatively impacts farmers’ livelihoods and agricultural sustainability, creating a cycle that hampers investment in modern farming technologies and sustainable practices. The study highlights the disproportionate access to credit, with institutional lenders favoring semi-medium, medium, and larger farmers, while small and marginalized farmers resort to non-institutional sources with higher interest rates. This unequal access perpetuates financial strain on the latter group. The findings emphasize the urgent need for government intervention and institutional support to assist marginalized and small farmers. The study advocates for comprehensive measures, including risk mitigation strategies, enhanced credit access, minimum support prices, and sustainable agricultural policies, to break the cycle of farmer debt and ensure the well-being of those crucial to our food systems.